Potenziale entwickeln und Wissen teilen: deutsche Unternehmen in Afrika; Developing potential and sharing knowledge: How German companies can gain a foothold in Africa - Dirk Dohse; Sophia Fehrenbacher; Philipp von Carlowitz (Wirtschaftsdienst, 2022)
Afrika ist ein Kontinent der Chancen, der in der künftigen weltwirtschaftlichen Arbeitsteilung eine deutlich größere Rolle spielen dürfte als bisher. Dennoch tut sich die deutsche Wirtschaft bislang schwer. Die digitale Transformation verändert die Investitions- und Innovationsbedingungen in Afrika. Daraus ergeben sich auch für deutsche Unternehmen Chancen auf dem afrikanischen Kontinent. Die Politik sollte Rahmenbedingungen für ein stärkeres privatwirtschaftliches Engagement deutscher und europäischer Unternehmen in Afrika schaffen. – – Africa is a continent of opportunities that is likely to play an increasingly important role in the future international division of labour. Yet, German companies' economic activity and investment in Africa is still limited. This article examines how the digital transformation is changing the investment and innovation conditions in Africa, how German companies can utilise new opportunities resulting from these changes and how politics can foster greater commitment by German and European companies in Africa.
Keywords: O25; O55; L25; 330; Auslandsinvestition; Subsahara-Afrika; Auslandsinvestition; Subsahara-Afrika